Increasing Buying Interest Halal Cosmetic Products Based on the Lifestyle of Millennial Consumers in Kendal Regency - Mutamimah, Mutamimah; Putriani, Nadila Sartika (Universitas Islam Sultan Agung, 2024)
Buying interest arises after going through the process of evaluating alternatives, during which an individual will formulate a decision plan regarding the product to be purchased based on interest or brand. The purpose of this research is to understand the influence of religiosity and halal knowledge on purchasing interest through lifestyle. The analysis method used in this study is explanatory research with a quantitative approach. In this study, the sample used consisted of 138 Millennial consumers in Kendal Regency Data collection was done through an online questionnaire. The analysis in this research utilized regression analysis with SPSS 26 software package, and the Sobel test was used to examine the influence of intervening variables. The results of this study indicate that religiosity significantly and positively affects lifestyle. Religiosity and knowledge of halal have a significant positive effect on lifestyle. Religiosity has a significant positive effect on buying interest. Halal knowledge does not have a significant positive effect on buying interest. Lifestyle has a significant positive effect on buying interest. The result for indirect influence, namely lifestyle, is able to mediate well between religiosity and halal knowledge on buying interest.